DIFFICULTIES RELATED TO INSULIN SELF-INJECTION: A LITERATURE REVIEW - Fernandes Garcês, Fábio (Health and Society, 2023)
This study aimed to identify the main difficulties related to self-injection of insulin. This is a literature review, with a qualitative approach, of a descriptive nature, carried out using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) tool, through the online search of national and international studies, in the period of July from 2023 to August 2023. Based on eligibility for the review, a total of 8 articles were selected for the study. According to the articles selected and analyzed, it is observed that the main difficulties are knowing the dosage, homogenization, lack of concrete information about this process, storage of the medicine and acceptance of the disease. The application of insulin was the most found in the studies, which is related to pain and fear, so this fact reflects on the patient’s self-confidence in managing their condition and consequently impairing their quality of life. Therefore, health professionals play an important role in the self-management of patients with diabetes, since support for self-administration of insulin is a necessary component in the care of people with chronic diseases.